Analysis of Marketing Strategy of Gold Savings Products in an Effort to Attract Customer Interest at Bank Syariah Indonesia (Case Study of Bank Syariah Indonesia KCP Marelan) - Harahap, Andi Hotmatua; Daulay, Aqwa Naser; Inayah, Nurul (Journal of Management and Administration Provision, 2025)
Bank Syariah Indonesia (BSI) is currently facing increasing competition among banking institutions, prompting each bank to enhance service quality and diversify product offerings. In response, an effective marketing strategy is essential to increase public interest, particularly in gold savings products. This study aims to determine the marketing strategy used to attract customers to gold savings at Bank Syariah Indonesia KCP Marelan. The research employs a descriptive method with a qualitative approach. Data sources include both primary data, obtained through observations and interviews, and secondary data. A SWOT analysis is utilized to identify internal and external factors influencing the bank's marketing strategy. The results of the study indicate that BSI KCP Marelan falls into quadrant I of the SWOT matrix, which represents a strong and opportunistic position. This suggests that the bank possesses significant internal strengths and is well-positioned to capitalize on external opportunities. The recommended marketing strategy is the SO (Strength-Opportunity) strategy, which involves using internal strengths such as rising gold prices and adherence to sharia principles to leverage external opportunities. This strategy includes promoting the security and religious alignment of gold savings to build customer trust, introducing the product more widely, and ensuring that pricing remains accessible. The bank’s position in quadrant I enables it to act aggressively and proactively in the market, allowing it to achieve marketing targets effectively. Overall, the study highlights the importance of aligning strengths with opportunities in order to develop an optimal marketing strategy for increasing customer interest in gold savings products at BSI KCP Marelan.